GAMBARAN ACADEMIC BURNOUT MAHASISWA TINGKAT AKHIR YANG BEKERJA - Aini, Nurul; Sulaiman, Sulaiman (Yayasan Nuraini Ibrahim Mandiri, 2024)
Burnout can cause physical health problems (decreased sleep quality, decreased concentration, reduced energy), emotional decline and depression (Maslach in Tandilangi, 2022). The burnout experienced by students is known as academic burnout, which has an impact on the lecture process not being optimal (Akladiwa, 2022). For working students, the demands of college assignments and work mean that students must be able to complete them simultaneously, causing a lot of stressors. This research used total sampling with a total of 16 respondents. The research results showed that the majority of respondents were aged 22 - 24 years old, 10 people (62.50%), with 9 people (56.25%) female. The research results showed that 9 people (56.25%) experienced moderate academic burnout, with 9 people (56.25%) having moderate fatigue dimensions, 9 people (56.25%) with moderate depersonalization, and 8 people (50%) experiencing moderate decline in achievement. %).